Cusp relation for the Pauli potential - H. Levämäki; Á. Nagy; K. Kokko; L. Vitos (AMER PHYSICAL SOC, 2022)
In orbital-free density functional theory, only a Schrödinger-like equation has to be solved for the square root of the electron density. In this equation, however, there is an extra potential in addition to the Kohn-Sham potential, the so-called Pauli potential. Cusp relations are now presented for this Pauli potential for spherically symmetric systems.